Effectiveness of educational campaign in promoting knowledge and attitude of pressure ulcer among physical therapists working in tertiary care hospitals - Zafar, Mahat; Kashif, Muhammad; Bunyad, Salma; Arshad, Feryal; Albalwi, Abdulaziz; Hussain, Nouman (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: This study aimed to evaluate the effectiveness of an educational campaign in promoting knowledge and attitudes concerning pressure ulcers among physical therapists working in tertiary care hospitals. METHODOLOGY: This study quasi-trial was conducted from January to October 2021 in which 45 PTs who worked in Neuro-spinal units were selected by purposive sampling from five randomly selected tertiary care hospitals in Faisalabad. The participants completed a questionnaire regarding their knowledge and attitude regarding pressure ulcer prevention and treatment, and their pre-test scores were recorded. After the pre-test, the primary researcher reviewed the incorrect responses of participants to develop and offer educational materials about the prevention and care of pressure ulcers. The "Pieper Pressure Ulcer Test" was used to evaluate changes in physical therapists’ knowledge and attitudes toward pressure ulcer. SPSS 21 was used for the data analysis. RESULTS: The educational campaign had a significant effect on the knowledge and attitudes of PTs, with the mean of the pre-test true response of 31.65, the mean of the post-true response of 39.00, and the mean of the pre and post-incorrect response of 8.19, and 4.62 and don’t know answers of 5.04, and 1.38, respectively. Based on one sample t-test, pre-true responses showed a 95% CI difference between 28.99 to 35.53 with a significant p-value <.001 and post-true responses showed 36.63 to 41.36 with a significant p-value <.001. CONCLUSION: This study concluded that the educational campaign improved physical therapists’ knowledge and attitudes regarding pressure ulcers.